IRRITABLE BOWEL SYNDROME: THE ROLE OF GUT MICROBIOTA IN ETIOLOGY AND TREATMENT. A LITERATURE REVIEW - Magdalena Cieślik-Porębska; Agata Cieślik (International Journal of Innovative Technologies in Social Science, 2026)
Irritable bowel syndrome (IBS) is a common gastrointestinal disorder. Its etiology is thought to involve many factors. Recent reports suggest that gut microbiota disorders may play an important role in the pathophysiology of IBS. This opens the door to new treatment therapies. Aim: The aim of this article is to review the latest research on the impact of changes in the gut microbiota on IBS, as well as methods of therapy that influence the modulation of the gut microbiota. Material and methods: A literature review was conducted using the PubMed and Google Scholar databases. The focus was on studies published between 2015 and 2025. Results: Changes in the gut microbiota play a significant role in IBS. However, there is still much uncertainty surrounding the exact pathomechanisms underlying this process. The low-FODMAP diet alleviates symptoms and causes changes in microbiota. Probiotics show moderate effectiveness, while the results of fecal microbiota transplantation are often inconclusive. Conclusions: Further research is needed to determine the exact impact of gut microbiota on IBS. The low-FODMAP diet, probiotics, and fecal microbiota transplantation offer promising but inconclusive treatment results. Further standardized studies are needed to determine the best therapeutic strategies.